Parametric Optimization and Efficiency Assessment of Horizontal Earth Water Pipe Heat Exchanger (EWPHE) in the Context of Bangladesh (Journal of Engineering Science, 2024)
This study aimed to evaluate the efficiency of the Earth Water Pipe Heat Exchanger (EWPHE) system in Bangladesh through simulation and experimental work carried out at Joypurhat in Bangladesh during the coldest period of the year, January. Additionally, the study sought to establish the method for selecting optimal installation parameters of EWPHE to increase performance and efficiency. A simulation model was made in the TRNSYS (v16.0) platform to determine the optimum values of design parameters. The simulation was run by altering its operating parameters, such as the rate of water flow, length of the pipe, built materials of the pipe, and the diameter of the underground pipeline. According to the findings, pipe burial can be done to a depth of 3.5 meters to achieve optimal output. The results of comparing four distinct materials, namely GI, Steel, PVC, and HDPE, show that these materials' characteristics do not significantly affect how well the systems perform. Additionally, as the water flow rate is increased, it is shown that the EWPHE performance is declining. According to the simulation results, it is concluded that a pipe with a length of 50 meters would be sufficient in the proposed EWPHE system to reach an average temperature decrease from 35 °C to 27 °C. Subsequently, in the field experiment, the EWPHE system had an average efficacy of 55% throughout January, which is quite promising.Journal of Engineering Science 14(2), 2023, 79-88